TINGKAT EROSI PADA LAHAN YANG BERBATUAN DASAR BATUAN BEKU DAN BATUAN METAMORF DI DESA TAWANGREJO DAN GUNUNGGAGAJAH, KECAMATAN BAYAT, KABUPATEN KLATEN, PROVINSI JAWA TENGAH - Yudono, Andi Renata Ade; Sungkowo, Andi (Bumi Lestari; Vol 15 No 1 (2015))
The study area consists of 2 (two) landforms, the hill and the ridge. The hill and the ridge  with slope varied have different rock composition, such as igneous and metamorphic rocks. Besides that the landcover of the two landforms also has different variety. These characteristics are expected to affect the rate of erosion. The purpose of this study were (i) To analyze the characteristics of the land parameter from both landforms with different rock units, as the factors that influence the differences in the level of erosion (ii) To determine the difference of the rate of erosion at the igneous and metamorphic bed rocks. Research methodology that have done were survey and mapping. The level of erosion is known from the results of direct measurements by the method of small plots on each land unit. The survey results revealed that the rate of erosion on the rock units schist (metamorphic rocks) is greater than the unit gabbro rock (igneous). Differences in the level of erosion is influenced by rock units, thick soil, slope, and land use.
Keywords: Erosion, Igneous Rocks, Metamorphic Rocks.